Waqaf Digital Transformation Towards Better Management - Muchamad Bayu Aldi Pamungkas (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
In Indonesia, waqf has great economic and social potential, but its management often faces administrative obstacles, lack of accountability, and limited access to information. The implementation of digital technology, such as blockchain, platform-based applications, and data management systems, enables the waqf management process to become more transparent and structured. With digitalization, waqf managers can more easily track and report the use of waqf funds in real-time, thereby increasing public trust. Technology also facilitates public participation in waqf, especially among the younger generation, by providing faster and easier access through digital platforms. This study uses a qualitative descriptive method with secondary data collection from journals, articles, and related reports. The results show that digital transformation not only increases the social and economic impact of waqf, but also presents challenges such as low digital literacy, technology costs, and the need for supportive regulations. Collaboration between the government, waqf institutions, and technology providers is needed to create an inclusive and sustainable digital waqf ecosystem. Keywords: digital transformation, waqf, waqf management.